The relationship between the triglyceride glucose-waist height ratio and benign prostatic hyperplasia in middle-aged and elderly adults: a nationwide cohort study - Bing Li; Zhiqiang Zhang; Junping Li; Xiaoqiang Liu (BMC Urology)
Abstract Objective Currently, evidence regarding the relationship between variations in the Triglyceride Glucose-Waist-to-Height Ratio (TyG-WHtR) and benign prostatic hyperplasia (BPH) remains scarce. This study aimed to examine the potential association between alterations in TyG-WHtR and the risk of developing BPH. Methods This study enrolled 3,296 male participants aged ≥ 45 years from the China Health and Retirement Longitudinal Study (CHARLS). Multivariable logistic regression analysis combined with restricted cubic spline models was employed to explore the potential relationship between TyG-WHtR variation and the risk of developing BPH. Results Over a 4-year follow-up period, 267 individuals were diagnosed with BPH. Elevated TyG-WHtR values were significantly associated with a higher risk of BPH (OR = 1.20, 95% CI: 1.02–1.43, p = 0.031), demonstrating a clear dose–response trend (p = 0.01). Furthermore, subgroup analyses revealed that this positive correlation between TyG-WHtR and BPH risk was consistently observed across multiple stratifications. Conclusion These findings highlight the potential metabolic links between TyG-WHtR and BPH, and underscore the need for future longitudinal studies to explore whether targeting these pathways may aid in BPH prevention.